Synthesis and Antimicrobial Activity of Some [1, 2, 4]-Triazole Derivatives. (8th November 2012) - Patil, Bhimagouda S.; Krishnamurthy, G.; Shashikumar, N. D.; Lokesh, M. R.; Bhojya Naik, H. S.
Abstract : A series of novel [1, 2, 4]-triazolo piperidine (8 ), [1, 2, 4]-triazolo piperazine (9a-c ), [1, 2, 4]-triazolo phenylether (10a-e ), and [1, 2, 4]-triazolo aniline (11a-c ) derivatives have been synthesized. The chemical structures of the newly synthesized compounds were characterized by IR, 1 H NMR, 13 C NMR, and LCMS. The newly synthesized compounds were screened for antimicrobial activity. Among all the compounds tested, 11b (R 4 = 4 -MeO–) showed the highest activity against Staphylococcus aureus and Escherichia coli, and 9 a (R1 and R 2 = Cl ) showed the highest activity against Pseudomonas Aeruginosa .